Photoinduced Ethylene Polymerization on Titania Nanoparticles. Issue 23 (9th November 2017) - Barzan, Caterina; Mino, Lorenzo; Morra, Elena; Groppo, Elena; Chiesa, Mario; Spoto, Giuseppe
Abstract: Herein, we report on the ability of H2 ‐photoreduced TiO2 nanoparticles to catalyze the polymerization of ethylene without the use of an alkylating agent. Even more, we demonstrate that the same reaction occurs directly on stoichiometric TiO2 in the presence of ethylene under UV‐light irradiation at room temperature and, thus, without any prereduction step. The synergic use of electron paramagnetic resonance and diffuse reflectance UV/Vis‐near‐IR spectroscopy allowed us to identify and correlate different Ti 3+ EPR signals and UV/Vis‐NIR bands, whereas transmission FTIR spectroscopy (applied under in situ UV‐light irradiation) was fundamental to prove ethylene polymerization and to observe ethylene oxidation byproducts. The possibility to polymerize ethylene easily in a one‐step procedure can be a promising approach to increase the compatibility of TiO2 as an inorganic additive for polyethylene blends. Abstract : One‐step is better : UV‐light irradiation of TiO2 nanoparticles leads to the successful one‐step production of a TiO2 /high‐density polyethylene (HDPE) composite without the use of any alkylating agent or prereduction step. The possibility of polymerizing ethylene in a one‐step procedure can be a promising approach to increase the compatibility of TiO2 as an inorganic additive for polyethylene blends.